Graphics' design work / Nurpuspawati Abdullah - Abdullah, Nurpuspawati (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
The traditional dessert of "Segurut" (Kuih Celorot) from Melanau symbolizes the uniqueness of Malaysian food culture. This artwork explores the visual characteristics of “Segurut” through the understanding of media dimensions which highlights the elements of structure, form, colors, pattern and proportion of “Segurut”.